2018
DOI: 10.1159/000488410
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin-2 Triggers Cervical Carcinoma Cell Hela Apoptosis via Mitochondrial Pathway in Mouse Model

Abstract: Background/Aims: Cervical carcinoma continues to be one of the most dangerous cancer types, and more effective therapies are urgently needed for cervical carcinoma treatment. Mitochondria-associated Mitofusin 2 has influence on the progression of many cancers. In the current study, we aimed to focus on the cell apoptotic effects of Mfn2 on cervical carcinoma HeLa cells in vitro and to try to explore its underlying mechanisms. Moreover, we investigated the anticancer potential of Mfn2 in a cervical carcinoma mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…32 MFN2 can also suppress cervical cancer progression through mitochondrial pathway. 33 Emerging evidence has shown that TGF-b1/Smad signaling regulates liver fibrosis. 23,24 Blocking Smad3 signaling could suppress type I collagen expression and inhibit epithelial-myofibroblast transition.…”
Section: Discussionmentioning
confidence: 99%
“…32 MFN2 can also suppress cervical cancer progression through mitochondrial pathway. 33 Emerging evidence has shown that TGF-b1/Smad signaling regulates liver fibrosis. 23,24 Blocking Smad3 signaling could suppress type I collagen expression and inhibit epithelial-myofibroblast transition.…”
Section: Discussionmentioning
confidence: 99%
“…It's well known that pro-apoptotic proteins, such as Bak and Bax, activate apoptosis, while anti-apoptotic Bcl-2 family proteins, such as BclXL and Bcl-2, inhibit apoptosis [28,29]. A increased ration of Bax/Bcl-2 could result in the release of cytochrome c from mitochondria and activation of caspase-3 and caspase-9, thereby inducing apoptosis through the mitochondria-associated apoptotic pathway [30]. In this study, we observed that Bax/Bcl-2, caspase-3 activity and caspase-9 activity were upregulaged after WJT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It's well known that pro-apoptotic proteins, such as Bak and Bax, activate apoptosis, while anti-apoptotic Bcl-2 family proteins, such as BclXL and Bcl-2, inhibit apoptosis [28,29]. A increased ration of Bax/Bcl-2 could result in the release of cytochrome c from mitochondria and activation of caspase-3 and caspase-9, thereby inducing apoptosis through the mitochondria-associated apoptotic pathway [30]. In this study, we observed that Bax/Bcl-2, caspase-3 activity and caspase-9 activity were upregulated after WJT treatment.…”
Section: Discussionmentioning
confidence: 99%